Medical students’ perceptions of LGBTQ+ healthcare in Singapore and the United Kingdom - Fu, Michael X.; Zou, Tangming; Aiyappan, Raksha; Ye, Xinyu; Onanuga, Simisola; Tan, Angela; Smith, Susan; Baptista, Ana (Frontiers in Medicine, 2023)
Introduction: Lesbian, gay, bisexual, transgender, queer, and other sexual and gender minority (LGBTQ+) individuals face many barriers to accessing healthcare. LGBTQ+ healthcare education remains scarce, and students’ understanding of LGBTQ+ healthcare remains largely uncharacterised. This study investigated the knowledge of and attitudes toward LGBTQ+ healthcare among medical students in Singapore and the United Kingdom (UK), two culturally different countries. Methods: Students in two medical schools, one in Singapore and the other in the UK, completed self-administered surveys using multiple-choice, Likert scale, and free-text questions to explore their ideas, concerns, and expectations about LGBTQ+ healthcare education within their medical curricula. Results: From 330 responses, knowledge levels were moderate with pronounced gaps in certain areas. Deficiencies were significantly greater among Singapore students compared to the UK (p<0.001), whilst LGBTQ+ students and non-religious students had more positive knowledge and attitudes than students not identifying. At least 78% of students had positive attitudes, but 84% had not received LGBTQ+-specific medical education. Although junior UK students were more satisfied with the adequacy of teaching by their medical school’s incorporation of LGBTQ+ inclusive teaching in a newer curriculum, qualitative analyses suggested that students in both countries wanted to receive more training. Conclusions: Students lacked understanding of commonly-used terminology and topics despite affirming attitudes towards LGBTQ+ healthcare. Although sociolegal contexts may affect students’ perspectives, differences were less than thought, and students were equally keen to provide affirmative care to their patients. They emphasised a need for more formal teaching of LGBTQ+ healthcare to overcome healthcare disparities.